Aerobic and resistance exercise training reverses age‐dependent decline in NAD+ salvage capacity in human skeletal muscle. Issue 12 (17th June 2019) - de Guia, Roldan M.; Agerholm, Marianne; Nielsen, Thomas S.; Consitt, Leslie A.; Søgaard, Ditte; Helge, Jørn W.; Larsen, Steen; Brandauer, Josef; Houmard, Joseph A.; Treebak, Jonas T.
Abstract: Aging decreases skeletal muscle mass and strength, but aerobic and resistance exercise training maintains skeletal muscle function. NAD + is a coenzyme for ATP production and a required substrate for enzymes regulating cellular homeostasis. In skeletal muscle, NAD + is mainly generated by the NAD + salvage pathway in which nicotinamide phosphoribosyltransferase (NAMPT) is rate‐limiting. NAMPT decreases with age in human skeletal muscle, and aerobic exercise training increases NAMPT levels in young men. However, whether distinct modes of exercise training increase NAMPT levels in both young and old people is unknown. We assessed the effects of 12 weeks of aerobic and resistance exercise training on skeletal muscle abundance of NAMPT, nicotinamide riboside kinase 2 (NRK2), and nicotinamide mononucleotide adenylyltransferase (NMNAT) 1 and 3 in young (≤35 years) and older (≥55 years) individuals. NAMPT in skeletal muscle correlated negatively with age ( r 2 = 0.297, P < 0.001, n = 57), and VO2 peak was the best predictor of NAMPT levels. Moreover, aerobic exercise training increased NAMPT abundance 12% and 28% in young and older individuals, respectively, whereas resistance exercise training increased NAMPT abundance 25% and 30% in young and in older individuals, respectively. None of the other proteins changed with exercise training. In a separate cohort of young and old people, levels of NAMPT, NRK1, and NMNAT1/2 in abdominal subcutaneous adipose tissue were not affected by either age or 6 weeks of high‐intensity interval training. Collectively, exercise training reverses the age‐dependent decline in skeletal muscle NAMPT abundance, and our findings highlight the value of exercise training in ameliorating age‐associated deterioration of skeletal muscle function. Abstract : NAMPT is crucially important for maintaining skeletal muscle NAD + levels. We show that both endurance‐ and resistance‐type exercise training reverses the age‐dependent decline in skeletal muscle NAMPT abundance. Our findings highlight the value of exercise training in ameliorating age‐associated deterioration of skeletal muscle function.